2019
DOI: 10.3153/fh19022
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Citrus Fiber Added Ground Beef and Consumer Acceptance of Citrus Fiber Added Turkish Meat-Balls

Abstract: The objectives of this study were (I) to determine the addition of different citrus fiber (CF) levels (0%, 1%, 5%, and 10%) on the quality attributes of ground beef meatballs, (II) to determine consumer preferences for ground beef meatballs made with different CF levels (0%, 1%, 3% and 5%). Both water holding capacity and cooking yield of samples significantly (p<0.05) increased with addition of citrus fiber. There is no significant (p>0.05) difference found between the control CF 0% and the CF 1% for hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Considering that the Cistus extract was obtained from all aboveground parts (including flowers, leaves, and particularly, stalks), it could contain fiber (Alves‐Ferreira et al, 2020). As it has been shown that fiber has a high water‐holding capacity (Gedikoğlu & Clarke, 2019; Madane et al, 2020), this could explain the higher WHC in the CC3 treatment. The water activity of cocktail sausages was affected by both the treatment and storage ( p < .05).…”
Section: Resultsmentioning
confidence: 94%
“…Considering that the Cistus extract was obtained from all aboveground parts (including flowers, leaves, and particularly, stalks), it could contain fiber (Alves‐Ferreira et al, 2020). As it has been shown that fiber has a high water‐holding capacity (Gedikoğlu & Clarke, 2019; Madane et al, 2020), this could explain the higher WHC in the CC3 treatment. The water activity of cocktail sausages was affected by both the treatment and storage ( p < .05).…”
Section: Resultsmentioning
confidence: 94%
“…Sample preparation was performed following a method previously described by Gedikoğlu and Clarke (2019). After the meat samples were ground, they were separated into four treatment groups, and prepared according to their citrus fibre levels (i.e., 0, 1, 3, and 5%) using CitraFiber™.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Therefore, antioxidant-rich fibre obtained from the citrus industry has great potential to be incorporated as a functional ingredient in comminuted meat products. It has been found that citrus fibre has great water-and oil-holding capacities (Lario et al, 2004;Berk, 2016;Gedikoğlu and Clarke, 2019). Also, due to the presence of antioxidants, citrus fibre has been shown (by using the thiobarbituric acid reactive substances [TBARS] assay) to delay lipid oxidation in meat products such as bologna sausage (Fernández-Ginés et al, 2003), Swedish meatballs (Fernández-López et al, 2005), dry-cured sausages (Fernández-López et al, 2007), minced fish (Sánchez-Alonso et al, 2007), and chicken hamburgers (Sáyago-Ayerdi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [ 11 ] added citrus fiber to gluten-free corn breads, which showed that citrus fiber can improve the WHC of bread, and the incorporation of citrus fiber reduced the firmness of bread. Gedikoğlu and Clarke reported that all ground beef meatballs with citrus fiber were lower in saturated fatty acids and higher in dietary fiber compared to the control samples [ 12 ]. The authors of [ 13 ] added citrus fiber to sausage and found it can also decrease residual nitrite levels.…”
Section: Introductionmentioning
confidence: 99%